Renoprotection Provided by Additional Diuretic Treatment in Partially Nephrectomized Ren-2 Transgenic Rats Subjected to the Combined RAS and ETA Blockade - Vaněčková, Ivana; Hojná, Silvie; Vernerová, Zdenka; Kadlecová, Michaela; Rauchová, Hana; Kompanowska-Jezierska, Elzbieta; Vaňourková, Zdeňka; Červenka, Luděk; Zicha, Josef (Frontiers in Physiology, 2019)
Objective: Our previous study in heterozygous Ren-2 transgenic rats (TGR) demonstrated that long-term treatment with endothelin receptor A (ETA) blocker atrasentan added to the renin-angiotensin system (RAS) blockade had renoprotective effects in a model of chronic kidney disease induced by partial nephrectomy. Since ETA blockade is known to cause edema, we were interested whether diuretic treatment added to this therapy would be beneficial. Design and Methods: Partial nephrectomy (NX) was performed at the age of 3 months in TGR rats which were subjected to: i) RAS blockade alone (angiotensin receptor blocker losartan and angiotensin converting enzyme inhibitor trandolapril), ii) combined RAS (losartan and trandolapril) and ETA receptor blockade (atrasentan), or iii) diuretic (hydrochlorothiazide) added to the combined RAS+ETA blockade for 50 weeks following NX. Results: At the end of the study systolic blood pressure and cardiac hypertrophy were similarly decreased in all treated groups. Survival was significantly improved by ETA receptor blockade added to RAS blockade with no further effects of diuretic treatment. However, additional diuretic treatment combined with RAS+ETA blockade decreased body weight and had beneficial renoprotective effects – reductions of both kidney weight and kidney damage markers. Proteinuria gradually increased in rats treated with RAS blockade alone, while it was substantially lowered by additional ETA blockade. In rats treated with additional diuretic, proteinuria was progressively reduced throughout the experiment. Conclusions: A diuretic added to the combined RAS and ETA blockade has late renoprotective effects in chronic kidney disease induced by partial nephrectomy in Ren-2 transgenic rats. The diuretic improved: renal function (evaluated as proteinuria and creatinine clearance), renal morphology (kidney mass, glomerular volume), and histological markers of kidney damage (glomerulosclerosis index, tubulointerstitial injury).